Targeting insulin-like growth factor-binding protein-3 by microRNA-125b promotes tumor invasion and poor outcomes in non-small-cell lung cancer - Hsiu-Hua Wang; Yao-Chen Wang; De-Wei Wu; Chin-Sheng Hung; Chih-Yi Chen; Huei Lee (Tumor Biology)
Insulin-like growth factor-binding protein-3 acts as a tumor suppressor that inhibits the PI3K/AKT signaling pathway due to blocking insulin growth factor-1 binding to its receptor. We hypothesized that insulin-like growth factor-binding protein-3 might be targeted by microRNA-125b and promote tumor invasion and poor outcome in non-small-cell lung cancer via activation of the PI3K/AKT signaling pathway. Real-time polymerase chain reaction and immunohistochemistry were performed to determine the level of microRNA-125b, insulin-like growth factor-binding protein-3 messenger RNA, and phosphorylated-AKT expression in 105 tumors from non-small-cell lung cancer patients. Low insulin-like growth factor-binding protein-3 messenger RNA levels and positive phosphorylated-AKT expression were more commonly found in patients with high microRNA-125b tumors than low microRNA-125b tumors. A poorer overall survival and relapse-free survival were observed in patients with high microRNA-125b tumors than low-microRNA-125b tumors in p53-mutated patients, but not in p53-wild-type patients. Mechanistically, microRNA-125b promotes invasion ability in p53-mutated cells via the PI3K/AKT activation by targeting of insulin-like growth factor-binding protein-3, but this effect was not observed in p53-wild-type cells. An increase in phosphorylated-AKT expression due to targeting of insulin-like growth factor-binding protein-3 by microRNA-125b was responsible for cell invasion in p53-mutated cells. In conclusion, the microRNA-125b level promotes invasive ability in p53-mutated cells via PI3K/AKT activation by targeting of insulin-like growth factor-binding protein-3, thereby resulting in p53-mutated non-small-cell lung cancer patients with poor outcomes.